NSAIDS versus electro-acupuncture in management of low back pain in patients with lumbar spondylosis: a comparative cohort study - Le, Ho Bao Chau; Tran, Nguyen Trong Phu; Nguyen, Thi Xuan Huynh (Tạp chí Y Dược Huế, 2024)
Background: Low back pain in lumbar spondylosis remains one of the most prevalent conditions, imposing a significant socio-economical burden. Objectives: To compare the effectiveness of low back pain treatment between NSAIDS and electro-acupuncture combined with infrared light (TCM) in patients with lumbar spondylosis. Materials and methods: We conducted a non-randomized prospective cohort study on lumbar spondylosis patients who had low back pain treated with either methods: NSAIDS or electro-acupuncture combined with infrared light therapy. Results: 75 patients were included, with a mean age of 53.39 ± 10.61 years. After 8 weeks of treatment, VAS scores decreased significantly from 7.5 ± 0.6 to 2.85 ± 0.4, p-value < 0.05 in NSAIDS group and from 5.8 ± 0.9 to 2.7 ± 0.6, p-value < 0.05 in TCM group. Schober index significantly increased over time (NSAIDS group from 10.36 ± 0.5 to 13.48 ± 0.7, TCM group from 10.88±0,8 to 13.61 ± 0.7, both with p-values < 0.05), whereas ODI score in both groups decreased (NSAIDS group from 37.4 ± 5.5 to 22.2 ± 5.5, TCM group from 28.68 ± 5.4 to 15.13 ± 6.4, with p-values < 0.05). The magnitude of improvement in VAS scores, Schober index, and ODI scores were more profound in NSAIDS group, with p-values < 0.05. Side effect associated with TCM treatment was seen in 8% of cases with pain at acupunture sites. Meanwhile in NSAIDS group, dyspepsia and flatulence were fairly common, at 24%. Conclusions: The use of NSAIDs in the management of low back pain in lumbar spondylosis patients is associated with better outcomes compared to TCM, with a trade-off for a higher risk of treatment-related side effects